Army of the Roman emperors - Fischer, Thomas (Casemate, 2019)
An illustrated history exploring the Imperial Roman army's many facets, including uniforms, weapons, buildings, and their duties. Compared to modern standard, the Roman army of the Imperial era was surprisingly small. However, when assessed in terms of their various tasks, they by far outstrip modern armies-acting not only as an armed power of the state in external and internal conflicts, but also carrying out functions nowadays performed by police, local government, customs, and tax authorities, as well as constructing roads, ships, and buildings. With this volume, Thomas Fischer presents a comprehensive and unique exploration of the Roman military of the Imperial era. With over 600 illustrations, the costumes, weapons and equipment of the Roman army are explored in detail using archaeological finds dating from the late Republic to Late Antiquity, and from all over the Roman Empire. The army's buildings and fortifications are also featured. Finally, conflicts, border security, weaponry, and artifacts are all compared, offering a look at the development of the army through time. This work is intended for experts as well as to readers with a general interest in Roman history. It is also a treasure-trove for re-enactment groups, as it puts many common perceptions of the weaponry, equipment, and dress of the Roman army to the test